2014
DOI: 10.1253/circj.cj-14-0985
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling New Therapeutic Targets of Coronary Artery Disease by Genetic Approaches

Abstract: Coronary artery disease (CAD) is the most common cause of death and physical disabilities in developed countries, even though efforts to identify and target causal factors such as hypertension and dyslipidemia have brought tremendous improvements in prevention and treatment. A rapid advance in technology has unraveled new genetic variants associated with CAD and also provided great opportunities to identify novel pathogenic mechanisms and to develop new drugs with higher specificity. Whole-genome sequencing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…7 A plethora of evidence confirmed the potency of members of family long PTX (PTX-3) in promoting atherosclerosis. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A plethora of evidence confirmed the potency of members of family long PTX (PTX-3) in promoting atherosclerosis. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 12 In spite of these modulations, many attempts have been focused on the application of natural compound and alternative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Better measures of exposure to the agents in the physical and social environments are critical to understanding the interrelationship among the specific genetic attributes, pathophysiology, and disease. Better evaluation of exposures to agents of disease and determinants of the phenotype, as well as newer, lower-cost genomic analyses, will more likely lead to advances in genetic epidemiology (113)(114)(115)(116)(117). Again, these studies will greatly benefit from new technologies and better and lower-cost data-collection methods for the investigation of epidemics.…”
Section: Mode Of Transmission Of Diseasementioning
confidence: 99%
“…Recent reports suggested that mutations in this gene cause small cell carcinoma of the ovary of hypercalcemic type [ 18 ], lung cancer [ 19 ], and other diseases [ 20 , 21 ]. Combining GWAS data and case-control studies, we reported the association of SMARCA4 with CAD risk [ 22 24 ]. To date, however, no studies investigated the possible correlations between SH2B3 and SMARCA4 genes and CAD susceptibility in the Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%